Effect of visual perception, visual function, cognition, and personality on power wheelchair use in adults. - Massengale S; Folden D; McConnell P; Stratton L; Whitehead V (Assistive Technology)
The purpose of this study was to determine to what extent visual perception, visual function, cognition, and personality traits affect power wheelchair use in adults. It also proposes to establish baseline information to help clinicians determine or predict power wheelchair driving performance and to develop service plans to address those driving skills that need improvement or compensation. Sixty-two adult power wheelchair users were recruited. Standardized instruments were used to evaluate visual perceptual skills, visual function, cognitive skills, and personality traits. The results of these evaluations were then correlated with participants' scores on a power wheelchair performance test. Strong correlations were found between power wheelchair driving performance and visual perception (p = .000), ocular motor function (p = .000 and p < or = .001), stereodepth perception (p < or = .001), and alertness to the environment (p < or = .001). No significant correlations were found between personality traits and power wheelchair driving performance. These results indicate that good visual perceptual skills, visual function, and various aspects of cognition are necessary for proficient power wheelchair use. These data will assist clinicians in identifying significant factors to consider when evaluating and training clients for power wheelchair use.